“Sedekah Bumi” Tradition as Local Wisdom of Coastal Javanese Society: Exploring The Human-Nature Relation through the Psychological Construct of Gratitude and the Ecocentrism Paradigm - Jessica Pramesti Pranoto; Marselius Sampe Tondok (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
“Sedekah bumi” known as earth alms is a traditional Javanese ceremony to express their gratitude to God Almighty. This tradition is linked to the relationship between humans and nature as studied within the ecocentrism paradigm. This study aims to explore the psychological construct of gratitude within the ecocentrism paradigm in “Sedekah Bumi” tradition as local wisdom. The methods used weare interviews and literature reviews. The interviewed participants were obtained using a purposive sampling method, and a narrative literature review was employed. . The results show that there are three themes from the interviews (Earth Almsgiving as a tradition, implementing the Earth Almsgiving Tradition, and the meaning of gratitude in the Earth Almsgiving Tradition). Meanwhile, the results of the literature review reveal three main meanings: social gratitude, gratitude to God, and human concern for the environment)). that the Javanese Coastal Community carried out the Earth Alms Tradition as a form of gratitude for the harvest that shows how humans not only receive the produce of the land but also care for it by working together to clean the environment. This concept is in line with the ecocentrism paradigm which describes all biotic and abiotic creatures as important because they can help human survival. Furthermore, with the escalating environmental crisis, these locally rooted traditions based on wisdom and eco-centrism can serve as alternatives in maintaining harmony between humans and nature.